Keabsahan Transaksi Live Shopping dari Asas Konsensualisme - Nayla S. Lestari; Zahra Asifa; Puput Dahlia; Novia Fadilah Akbar; Ikhwan Aulia Fatahillah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid development of information technology has contributed to the emergence of various forms of electronic transactions, one of which is live shopping, which combines product promotion and purchasing activities through digital platforms. Although conducted without direct physical interaction between sellers and buyers, live shopping transactions still create legal relationships that generate rights and obligations for the parties involved. This study aims to analyze the validity of live shopping transactions from the perspective of the consensualism principle in Indonesian contract law, examine the legal position of electronic evidence as a means of proof, and identify legal protection and dispute resolution mechanisms available in cases of breach of contract. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research by examining laws and regulations, legal literature, scientific journals, and other relevant legal sources. The findings indicate that live shopping transactions constitute valid electronic agreements as long as they fulfill the legal requirements of a contract as stipulated in Article 1320 of the Indonesian Civil Code. The principle of consensualism serves as the basis for the formation of legal relationships through the mutual consent of the parties, even when conducted electronically. Furthermore, the Electronic Information and Transactions Law recognizes electronic documents and electronic information as legally valid evidence, thereby providing legal certainty in dispute resolution. Therefore, live shopping transactions possess the same legal validity and legal consequences as conventional transactions.